2011
DOI: 10.1007/s11655-011-0690-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fufang Xueshuantong Capsule (复方血栓通胶囊) on a rat model of retinal vein occlusion

Abstract: A rat model of laser photothrombosis-induced RVO was established and an increase in the VEGF expression was observed in the retinal lesion. The FXC had therapeutic benefit in improving retinal lesions in the rat model of RVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…To validate zebrafish thrombosis model for pharmaceutical testing, six marked human antithrombotic drugs aspirin (thromboxane A2 inhibitor), 13 clopidogrel (ADP inhibitor), 14 diltiazem hydrochloride injection (calcium channel blocker), 15 xuanshuantong injection (inhibiting platelet aggregation, blood coagulation, fibrinolysis activation, and reducing plasma viscosity), 17 salvianolate injection (antiplatelet aggregation, anticoagulant, and antithrombosis), 36 and astragalus injection (restraining thrombosis and platelet aggregation) 37 were chosen and tested in this model for preventive and therapeutic effects on thrombosis. All six human antithrombotic drugs significantly reduced zebrafish thrombosis after 24 h cotreatment (thrombosis prevention) or treatment (thrombus therapy), indicating that the zebrafish thrombosis model developed in this report is suitable for in vivo screening and assessment of oral and injectable antithrombotic drugs no matter as a single compound medicine or a herb extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate zebrafish thrombosis model for pharmaceutical testing, six marked human antithrombotic drugs aspirin (thromboxane A2 inhibitor), 13 clopidogrel (ADP inhibitor), 14 diltiazem hydrochloride injection (calcium channel blocker), 15 xuanshuantong injection (inhibiting platelet aggregation, blood coagulation, fibrinolysis activation, and reducing plasma viscosity), 17 salvianolate injection (antiplatelet aggregation, anticoagulant, and antithrombosis), 36 and astragalus injection (restraining thrombosis and platelet aggregation) 37 were chosen and tested in this model for preventive and therapeutic effects on thrombosis. All six human antithrombotic drugs significantly reduced zebrafish thrombosis after 24 h cotreatment (thrombosis prevention) or treatment (thrombus therapy), indicating that the zebrafish thrombosis model developed in this report is suitable for in vivo screening and assessment of oral and injectable antithrombotic drugs no matter as a single compound medicine or a herb extract.…”
Section: Discussionmentioning
confidence: 99%
“…16 Xueshuantong, an injectable drug extracted and prepared from an Chinese herb Panax notoginseng, has been used to treat thrombotic diseases in China for more than 30 years and has been proved highly effective. 17 Salvianolate prepared from a Chinese herb Salvia miltiorrhiza is a commonly used medicine for ''invigorating'' the blood and reducing blood clotting in eastern countries, particularly in China, and many studies have shown that salvianolate can inhibit platelet aggregation and adhesion and reduce thrombus formation. 18 Astragalus as a TCM has been used for thousands of years, and recently, mainly for treating thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, FFA is recommended for studies on retinal vessel diseases. In this research, the injected concentrations and volumes of contrast agent were obtained from literature review [22][23][24][25][26] and our experimental experience. At high concentrations, signals rose faster and higher to reveal the overall vascular structure quickly and in detail.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesised that as the major component in the Honghua extract is glucose, the neuroprotective effect of the same could be due to availability of energy source after ischemia (Romano, et al, 1993). Another Chinese herbal medicine -Fufang Xuehuantong capsule was also studied by Yuan et al They created a rat model for retinal vein occlusion by using laser photocoagulation and then validated the therapeutic benefits Chinese herbal medicine by quantitating the expression of various growth factors in the animal model (Yuan et al, 2011).…”
Section: Photocoagulation Of Retinal Vesselsmentioning
confidence: 99%